Primary Signet-Ring Cell Adenocarcinoma of the Urinary Bladder Treated with Partial Cystectomy: A Case Report and Review of the Literature - Umesh Jayarajah; D. M. Hilary Fernando; Kasun Bandara Herath; M. V. Chandu de Silva; S. A. S. Goonewardena (Case Reports in Urology)
Primary signet-ring cell carcinoma is a variant of adenocarcinoma which is extremely rare, associated with poor prognosis and generally found to be resistant to chemotherapy and radiotherapy. We report a case of primary signet-ring cell carcinoma of the bladder which was successfully treated with partial cystectomy. A 71-year-old female with a history of type 2 diabetes, hypertension, and ischaemic heart disease presented with painless haematuria for 2 months’ duration. The abdominal ultrasonography showed a localised polypoidal vesical growth arising from the bladder dome. Cystoscopy revealed an exophytic solid tumour in the anterior fundal wall. A deep transurethral resection of bladder tumour was done and histology revealed an adenocarcinoma composed of mucinous and signet-ring cell components. Later, considering the patient’s age and the poor general condition, a partial cystectomy was done. Follow-up cystoscopy and ultrasonography were done at 12 months and there was no evidence of tumour recurrence and the patient is currently symptom-free. Partial cystectomy may be considered in patients with localised tumour without evidence of metastasis and poor general condition. Regular cystoscopies and ultrasound imaging are necessary for follow-up and early identification of recurrences.